Study protocol of D1Ce Screen: A pilot project of the Italian national screening program for type 1 diabetes and coeliac disease in the paediatric population - Olimpia Vincentini; Flavia Pricci; Marco Silano; Umberto Agrimi; Francesca Iacoponi; Marika Villa; Chiara Porfilio; Adalgisa Ilaria Sedile; Francesca Ulivi; Carlo Catassi; Valentino Cherubini; Antonio D’Avino; et al. (PLoS ONE, 2025)
Background The D1Ce Screen pilot study stems from the Italian Republic Law 130/2023 introducing the screening based on autoantibody measurement on capillary blood for the identification of people in pre-symptomatic, early phase of type 1 diabetes (T1D) and/or having silent celiac disease (CD) in the general paediatric population to reduce the impact of the two more frequent and severe chronic diseases of childhood. Aim Primary aim is to assess, on a smaller scale, the organizational feasibility, acceptability and sustainability by the National Health Service of the screening program to be conducted nationwide in Italy according to the law. Methods and analysis This is an observational multicenter study, planning to screen 5,363 children from four Italian regions (Lombardy, Marche, Campania, Sardinia), proportionally distributed according to population of the single Regions, representative of the North, Centre, South and Islands of Italy. Participants are screened by autoantibodies within three classes of age 2–2.9, 6–6.9, and 10–10.9 years, corresponding to reported peaks of seroconversion, in order to maximize the identification of future cases of disease. HLA typing for HLA DQ2 and DQ8 is also performed for CD risk in dry blood spots (DBS). Screening procedures are conducted by primary care paediatricians (PCPs), responsible for: direct contact with families; information about the study; administration of written informed consent, privacy statement and questionnaires; execution of blood drawing by finger prick; capillary blood collection for autoantibody and HLA testing and shipment to the central laboratory. Feasibility, acceptability and sustainability will be estimated by number of participating paediatricians; screened children in the four Regions and within the classes of age; feedback questionnaires; number of fingerpicks to obtain sufficient capillary blood for assays; any adverse events; costs evaluation in relation to assigned budget. Secondary objectives include frequency of T1D and CD specific autoantibodies to assess the prevalence of pre-symptomatic (Stage 1 and Stage 2) TD1 and undiagnosed CD in the three classes of age of general paediatric population. Study registration D1Ce Screen is not registered to any International Study Registry, as it is a pilot observational study requested by the Italian law 130/2023.